Dynamic loading induced by the instability of voussoir beam structure during mining below the slope. (August 2020) - Li, Zhu; Yu, Shengchao; Zhu, Weibing; Feng, Guorui; Xu, Jingmin; Guo, Yuxia; Qi, Tingye
Abstract: Dynamic loading events in the longwall faces under slopes in the Shendong Coalfield, China, seriously limit the safety and efficiency of mining. The slope characteristics, such as direction, height, and angle, determine the load type and the stability of the voussoir beam structure (VBS) formed by fractured blocks of the primary key stratum (PKS). Whether or not dynamic loading events will occur can be directly determined based on the presence or absence of a stable VBS in the PKS. Based on this relationship, six structural mechanical VBS models for different load distributions were established and then the effects of the slope direction, height, and angle on the stability of VBS was analysed. Changes of load type intensified the compression force between the hinged blocks. When the compression force between blocks exceeded the strength of the rock, VBS instability and dynamic loading events occurred. The compression force in the VBS increased with increasing slope angle and height when the slope directions were similar, becoming more pronounced for mining under the uphill sections of the slopes. Therefore, a method of determining the critical slope parameter values indicating a risk of dynamic loading was proposed, enabling such slopes to be recognised in advance. Measures such as slope top cutting or backfilling can then be applied to prevent potential dynamic loading accidents. This study can provide guidelines for safe mining under geological conditions involving widespread slopes and gullies.